Letter to Jane Tolmach from May Layne Bonnell - May Layne Bonnell:::::: (1961)
A letter to Jane Tolmach from May Layne Bonnell regarding a tape recording Tolmach made and that the press had seen Tolmach's letters, remarks, and were in possession of the tape. Details of the tape were not provided.